Representasi Gender dalam Cerita Rakyat Timun Mas: Antara Kemandirian dan Keterbatasan Peran Perempuan - Kapeanis, Anisa; Asrini, Hari Windu (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to examine language and gender representation in the folktale Timun Mas, focusing on the portrayal of women in the story. Using a critical discourse analysis approach and gender perspectives, this article investigates how the narrative in Timun Mas depicts the independence and limitations of women's roles within the context of a patriarchal culture. Although the main character, Timun Mas, is portrayed as brave and independent, the narrative still reveals a dependence on assistance from male characters, such as the hermit who provides help. Additionally, the mother's role in this story appears passive and reliant on male authority to save her child. The analysis results indicate an ambivalence in gender representation, where, despite a space for women to appear strong, their roles remain constrained by the patriarchal norms inherent in society. This research provides insights into how folklore functions as a medium for reproducing gender values in society, as well as the importance of critique against gender representation in traditional literary works.